#### Answer

See figure and explanations.

#### Work Step by Step

Step 1. We can identify two vertical asymptotes as $x=\pm2$
Step 2. We can identify a horizontal asymptotes as $y=1$
Step 3. The function is even because $f(-x)=f(x)$
Step 4. We can find the x-intercepts as $x=\pm1$
Step 5. We can find the y-intercept as $y=\frac{1}{4}$
Step 6. We can identify the signs across the vertical asymptotes and zeros as
$...(+)...(-2)...(-)...(-1)...(+)...(1)...(-)...(2)...(+)...$
Step 7. Based on the information above, we can graph the function as shown in the figure.